Faktor Penghambat dalam Pelaksanaan Program VCT (Voluntary Counselling And Testing): A Literature Review - Nita Anggerina Putri Hi Setiawan; Mateus Sakundarno Adi (FORIKES, 2020)
The prevalence of HIV/AIDS had been increasing due to the lack of awareness of people to use or access VCT services, especially those with high risk. Many factors affect people and people at high risk of accessing VCT services. The study aims to describe barriers that arise in the implementation of the VCT program. The research method was a literature review from electronic database such as Google Scholar, PubMed, and Science Direct. Keyword search included barrier, Voluntary Counseling and Testing, and HIV VCT. Selected 9 articles published from 2018 to 2020. The results of the study of all articles founded that barriers in the implementation of VCT in the form of lack of knowledge, fear, and shame when taking an HIV test, difficulty in communicating because of hearing impairment so that the information received was not enough, stigma from the community and health workers, barriers to limited operational hours of VCT services, lack of staff as program implementers, limited competence due to lack of training, and limited health infrastructure/facilities. Keywords: barrier; VCT; HIV/AIDS ABSTRAK Prevalensi HIV/AIDS semakin meningkat karena kurangnya kesadaran orang-orang untuk memanfaatkan atau mengakses layanan VCT terutama mereka dengan risiko tinggi. Banyak faktor yang mempengaruhi masyarakat maupun orang dengan risiko tinggi dalam mengakses layanan VCT. Tujuan penulisan artikel ini adalah untuk menggambarkan tentang hambatan-hambatan yang muncul dalam pelaksanaan program VCT. Metode penelitian adalah literature review dari database elektronik seperti Google Scholar, PubMed, dan Science Direct. Kata kunci pencarian antara lain menggunakan kata kunci barrier, Voluntary Counselling and Testing, dan VCT HIV. Terpilih 9 artikel yang dipublikasi tahun 2018 sampai 2020. Hasil penelitian dari semua artikel, diperoleh bahwa hambatan-hambatan dalam pelaksanaan VCT yaitu berupa kurangnya pengetahuan, rasa takut, dan malu jika melakukan tes HIV, kesulitan dalam berkomunikasi karena memiliki gangguan pendengaran sehingga informasi yang diterima pun kurang, stigma dari masyarakat serta petugas kesehatan, hambatan jam operasional layanan VCT yang terbatas, kurangnya jumlah staf sebagai pelaksana program, kompetensi yang terbatas karena kurang mengikuti pelatihan, serta infrastruktur/fasilitas kesehatan yang terbatas. Kata Kunci: hambatan; VCT; HIV/AIDS